2009
DOI: 10.1174/021347409789050560
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive and prescriptive features of gender stereotyping. Relationships among its components

Abstract: This paper explores the relation between gender stereotyping in traits and roles and sociodemographic variables, as well as the relation between the descriptive and prescriptive characteristics of such traits and roles. In Study 1, a representative national sample of 1255 participants was used. The results showed that trait stereotyping did not vary among participants, whereas role stereotyping did vary as a function of gender (women stereotyped less) age (young people stereotyped less) and educational level (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
2
5
0
2
Order By: Relevance
“…This finding is in line with the idea that people can have knowledge of collectively shared stereotypes with regard to SDS or personal stereotypical expectations about the sexual behavior of men and women, although they do not apply these stereotypes personally when evaluating other people's sexual behavior (Milhausen & Herold, 2001;Signorella et al, 1993). It has been argued that knowledge of collective stereotypes is strong, stable, and does not depend on one's experience with other people, but on culturally shared and generalized social beliefs (López-Sáez & Lisbona, 2009). Indeed, research in children as well as adults showed that content of collective gender stereotypes has not changed over time, whereas gender attitudes did become more egalitarian (e.g., Ruble, 1983;Signorella et al, 1993).…”
Section: Conceptualization and Measurement Of Sdssupporting
confidence: 82%
“…This finding is in line with the idea that people can have knowledge of collectively shared stereotypes with regard to SDS or personal stereotypical expectations about the sexual behavior of men and women, although they do not apply these stereotypes personally when evaluating other people's sexual behavior (Milhausen & Herold, 2001;Signorella et al, 1993). It has been argued that knowledge of collective stereotypes is strong, stable, and does not depend on one's experience with other people, but on culturally shared and generalized social beliefs (López-Sáez & Lisbona, 2009). Indeed, research in children as well as adults showed that content of collective gender stereotypes has not changed over time, whereas gender attitudes did become more egalitarian (e.g., Ruble, 1983;Signorella et al, 1993).…”
Section: Conceptualization and Measurement Of Sdssupporting
confidence: 82%
“…There was no such age difference with regard to the perceived belief of groups. These findings are consistent with previous literature (e.g., López-Sáez and Lisbona, 2009 ) that reports reduced discrepancies between the components of stereotyping as one's own cognitive structure and the perception of characteristics attributed by all (or most) individuals of a collective with increased age.…”
Section: Discussionsupporting
confidence: 93%
“…As a result, public contexts early in life may set the stage for the automatic activation and application of stereotypes (e.g., gender stereotypes) later in life. This processing mechanism is demonstrated by the finding that young people stereotype less than older people (López-Sáez and Lisbona, 2009 ). This development of stereotyping may be also reflected in the development of the discrepancy between one's own cognitive information processing structure in form of schemata (personal belief) and the perception of attributed characteristics by members of a collective (perceived belief of groups, Macrae et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios que recientemente han analizado la influencia concreta de diferentes variables socioculturales y sociodemográficas (ej., Castillo-Mayén y Montes-Berges, 2007; Diekman y Diekman et al, 2005;García-Retamero et al, 2009;López-Sáez y Lisbona, 2009;RochaSánchez y Díaz-Loving, 2005;Wilde y Diekman, 2005), indican, por ejemplo, que el tamaño poblacional incide sobre la aplicación de los estereotipos tradicionales (García-Retamero et al, 2009), o que la edad, sexo y nivel educativo influyen sobre la vigencia de la dimensión prescriptiva de los estereotipos de género, pero no sobre la dimensión descriptiva (Ló-pez-Sáez y Lisbona, 2009).…”
Section: Introductionunclassified